2003
DOI: 10.1094/mpmi.2003.16.9.743
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nops, Nodulation Outer Proteins, Secreted Via the Type III Secretion System of NGR234

Abstract: The nitrogen-fixing symbiotic bacterium Rhizobium species NGR234 secretes, via a type III secretion system (TTSS), proteins called Nops (nodulation outer proteins). Abolition of TTSS-dependent protein secretion has either no effect or leads to a change in the number of nodules on selected plants. More dramatically, Nops impair nodule development on Crotalaria juncea roots, resulting in the formation of nonfixing pseudonodules. A double mutation of nopX and nopL, which code for two previously identified secrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
169
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(193 citation statements)
references
References 40 publications
5
169
0
2
Order By: Relevance
“…These findings were consistent with the observation that a nopL mutant of NGR234 (strain NGR⍀nopL) induced fewer nodules on the legume Flemingia congesta (22). Experiments with recombinant NopL protein expressed in Escherichia coli revealed that NopL could be phosphorylated at unknown sites by nondefined protein kinases from crude plant protein extracts (23,24).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…These findings were consistent with the observation that a nopL mutant of NGR234 (strain NGR⍀nopL) induced fewer nodules on the legume Flemingia congesta (22). Experiments with recombinant NopL protein expressed in Escherichia coli revealed that NopL could be phosphorylated at unknown sites by nondefined protein kinases from crude plant protein extracts (23,24).…”
supporting
confidence: 88%
“…Plants were either inoculated with ϳ10 9 bacteria of Rhizobium (Sinorhizobium) sp. strain NGR234 or its nopL mutant NGR⍀nopL (22). For complementation analysis, plasmid pLAFR-pnopL (supplemental Table S1) was constructed and mobilized from E. coli DH5␣ into NGR⍀nopL by a triparental mating procedure using the pRK2013 "helper" plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, because type-three secretion by NGR234 has little effect on nodulation of L. japonicus, it is not an optimal plant to assess the function of NopL. Future work will focus on the interaction between F. congesta and NGR234, in which nopL has been shown to promote nodule formation (Marie et al, 2003). It will be interesting to see whether induced systemic resistance and/or systemic acquired resistance interfere with the establishment of mutualistic symbioses.…”
Section: Table I Plant Growth and Nodule Formation Of L Japonicus Pmentioning
confidence: 99%
“…This expression cassette was subcloned into the binary vector pPZP112 (Hajdukiewicz et al, 1994; yielding pPZP112nopL) and was transferred to A. tumefaciens by triparental matings using the helper plasmid pRK2013 (Figurski and Helinski, 1979). To produce recombinant protein, nopL was cloned into the pPROEX-1 vector (Invitrogen, Carlsbad, CA) to give pPROEX-1nopL (Bartsev et al, 2003;Marie et al, 2003). This vector added an in-frame hexa-His tag (6x-His) to the N terminus of NopL.…”
Section: Biological Materials and Vector Constructionmentioning
confidence: 99%
See 1 more Smart Citation